The Relationship Between Parents' Knowledge And Perception Towards Sexual Education Behavior Towards Early Childhood: Literature Review - Pramusti, Selvia Ratih; Adyani, Kartika (Universitas Prima Indonesia, 2026)
Cases of sexual violence against children in Indonesia continue to show an increasing trend, necessitating effective prevention efforts, one of which is through providing sexual education from an early age. In this regard, parents play a crucial role, influenced by their level of knowledge and perceptions regarding sexual education. This study aims to analyze the relationship between parental knowledge and perceptions and behavior in providing sexual education to early childhood. The method used was a systematic literature review, which searched articles in Google Scholar, PubMed, and ScienceDirect databases using relevant keywords. The inclusion criteria included articles published between 2015 and 2024, in Indonesian or English, and available in full-text format. The initial search identified 45 articles, and after a selection and screening process, 11 articles met the criteria for analysis. The results showed that most studies reported a significant relationship between parental knowledge and perceptions and behavior in providing sexual education to children. Parents with a good level of knowledge and positive perceptions tend to be more capable of providing appropriate sexual education to their children. Therefore, increasing knowledge and forming positive perceptions among parents is very necessary to support the provision of early sexual education as a step to prevent sexual violence against children.